RUBEM ALVES AND THE IDEOLOGY OF PLEASURE - Peixoto Filho, Fernando (2025)
Rubem Azevedo Alves (September 15, 1933 – July 19, 2014) is a multifaceted intellectual whose work remains vigorous and influential, and his texts still inspire millions of scholars in Brazil and around the world. The plural aspect of Alves' biography lies largely in his education, which was also multiple: psychoanalyst, theologian, pastor, and, above all, educator. He wrote in a variety of genres, from self-help to children's stories. It is important to recognize, however, that the core of Alves' literature lies in the pedagogical sphere. Rubem Alves is, above all, an educator. Based on this premise, this text proposes a reflection on the anthropological, linguistic, and ideological aspects present in Rubem Alves' work, examining biographical factors and delving into the terrain of his plural education, which definitively contributes to his pedagogical perspective. Taking as true the premise that ideology is contained and can be inferred from the work of any thinker, this work seeks to identify the anthropological-ideological marks in two exemplary texts in Alves' work: Urubus e Sabiás and Pinóquio às Avessas.